The Level of Patients Satisfaction In Pharmacy Installation of Langsa Regional Hospital - Diza Fathamira Hamzah; Sri Rosita; Rahmayani Rahmayani (Universitas Serambi Mekkah, 2022)
One of the hospital services is pharmaceutical service which is a service that must be provided by the hospital. Pharmaceutical service is a service which is directly responsible to patients related to pharmaceutical preparations with the aim of achieving definite results to improve the quality of life of patients in general, including patients using health social security administrator. This study aims to determine the analysis of the level of patient satisfaction in the Pharmacy Installation at Langsa Regional Hospital. The study population was all patients in the Pharmacy Installation of Langsa Regional Hospital and 79 of them was drawn as sample research by using accidental sampling technique.The data were collected by using questionairre. The data analysis was carried out univariately by identify the percentage of each variable studies. The results showed that 60 patients were unsatisfied (75.9%). In terms of several sub-assessments, 58 patients satisfied with the positive attitude of officers (73.4%), 62 patients (78.5%)unsatisfied with the waiting time of the services which is according to the standard besides 57 patients (72.1%)unsatisfied with the drug information service provided. It is necessary to improve the quality of pharmaceutical services by organizing training for health workers and evaluating services on a regular basis. Keywords: Patient Satisfaction, Public Health Status, Rational Use of Drug, Hospital Services